Molecular Epidemiology of Human Metapneumovirus in East Japan before and after COVID-19, 2017–2022 - Shirato, Kazuya; Suwa, Reiko; Nao, Naganori; Kawase, Miyuki; Sugimoto, Satoko; Kume, Yohei; Chishiki, Mina; Ono, Takashi; Okabe, Hisao; Norito, Sakurako; Sato, Masatoki; Sakuma, Hiroko; et al. (Japanese Journal of Infectious Diseases, 2024)
Human metapneumovirus (hMPV) is genetically classified into two major subgroups, A and B, based on attachment glycoprotein (G protein) gene sequences. The A2 subgroup is further separated into three subdivisions, A2a, A2b (A2b1), and A2c (A2b2). Subgroup A2c viruses carrying 180- or 111-nucleotide duplications in the G gene (A2c 180nt-dup or A2c 111nt-dup ) have been reported in Japan and Spain. The coronavirus disease 2019 (COVID-19) pandemic disrupted the epidemiological kinetics of other respiratory viruses, including hMPV. In this study, we analyzed the sequences of hMPV isolates in Tokyo and Fukushima obtained from 2017 to 2022, i.e., before and after the COVID-19 pandemic. Subgroup A hMPV strains were detected from 2017 to 2019, and most cases were A2c 111nt-dup, suggesting ongoing transmission of this clade, consistent with global transmission dynamics. Subgroup B viruses, but not subgroup A viruses, were detected in 2022 after the COVID-19 peak. Phylogenetic analysis showed that the subgroup B viruses were closely related to strains detected in Yokohama from 2013 to 2016, and strains detected in Fukushima in 2019, suggesting the reappearance of local endemic viruses in East Japan.